Chinese Environmental Humanities - Chang, Chia-ju (Palgrave Macmillan, 2019)
1. Environing at the Margins: Huanjing as a Critical Practice – Section I Chinese Ecocriticism and Ecotranslation Studies – 2. Building a Post-Industrial Shangri-La: Lu Shuyuan, Ecocriticism, and Tao Yuanming’s “Peach-Blossom Spring” – 3. The Nakedness of Hope: Solastalgia and Soliphilia in the Writings of Yu Yue, Zhang Binglin, and Liang Shuming – 4. Blurred Centers/Margins: Ethnobotanical Healing in Writings by Ethnic Minority Women in China – 5.From Jiang Rong to Jean-Jacques Annaud: An Ecological Rewrite of Wolf Totem – 6. An Ecotranslation Manifesto: On the Translation of Bionyms in Nativist and Nature Writing from Taiwan – Section II Chinese Ecocinema and Ecomedia Studies – 7. Worms in the Anthropocene: The Multispecies World in Xu Bing’s Silkworm Series – 8. Place, Animals, and Human Beings: The Case of Wang Jiuliang’s Beijing Besieged by Waste – 9. Land, Technological Triumphalism and Planetary Limits: Revisiting Human-Land Affinity – 10. Ecomedia Events in China: From Yellow Eco-Peril to Media Materialism – Section III Sustainability, Organic Community, and Buddhist Multispecies Ethics – 11 The Paradox of China’s Sustainability – 12 Contemplating Land: An Ecocritique of Hong Kong – 13. The Intersection of Sentient Beings and Species, Traditional and Modern, in the Practices and Doctrine of Dharma Drum Mountain – 14. An Exposition of the Buddhist Philosophy of Protecting Life and Animal Production Chinese Environmental Humanities showcases contemporary ecocritical approaches to Chinese culture and aesthetic production as practiced in China itself and beyond. As the first collaborative environmental humanities project of this kind, this book brings together sixteen scholars from a diverse range of disciplines, including literary and cultural studies, philosophy, ecocinema and ecomedia studies, religious studies, minority studies, and animal or multispecies studies. The fourteen chapters are conceptually framed through the lens of the Chinese term huanjing (environment or “encircling the surroundings”), a critical device for imagining the aesthetics and politics of place-making, or “the practice of environing at the margin.” The discourse of environing at the margins facilitates consideration of the modes, aesthetics, ethics, and politics of environmental inclusion and exclusion, providing a lens into the environmental thinking and practices of the world’s most populous society
10.1007/978-3-030-18634-0
Keywords: Aufsatzsammlung; Asian Literature; Oriental literature; Literature-Translations; Communication; Environmental sciences; Umwelt; Ökologie; Geisteswissenschaften; Sprache; Kritik; Linguistik; Film; Audiovisuelle Medien; Medienforschung; Gesellschaft; Religion; Ethik